Cervical stump leiomyomata after supracervical hysterectomy; a case report with review of literature - Ahmed Shoukry; Mahmoud Yousri (BMC, 2024)
Abstract Background Despite being a highly debated issue, subtotal or supracervical hysterectomy (SCH) is still considered a safe and effective treatment for women with benign gynecological lesions. Benign and malignant cervical diseases have been reported after SCH, with fibroids being the most frequently diagnosed lesions in the excised cervical stump. Recurrence of cervical disease after SCH usually presents with vaginal bleeding, pelvic mass, or abdominal pain; moreover, it may necessitate reoperation and resection of the cervical stump or trachelectomy. Trachelectomy is known to be a difficult surgical procedure that may be associated with significant intra- and post-operative morbidity. Case presentation We presented here a case of a 41-year-old nulliparous woman with a pelvic mass related to the cervical stump presented 2 years after subtotal hysterectomy, performed due to interactable abnormal uterine bleeding, which was attributed to a multiple fibroid uterus. Six years ago, she complained of pelvic pain, excessive vaginal discharge, and spotting. A transvaginal sonography and magnetic resonance imaging with contrast were performed, which revealed a 10.2 × 7.6 × 6.5 cm heterogeneous pelvic mass with irregular borders and marked vascularity on color Doppler. Surgical exploration and resection of the mass with cervical stump excision were performed. Histopathology confirmed the diagnosis of cervical stump multiple benign leiomyomata with no atypical features. Conclusion Recurrence or De novo development of leiomyomata and other cervical lesions might occur after supracervical or subtotal hysterectomy; thus, thorough pre-operative counseling for women requesting a SCH regarding the pros and cons of the procedure compared with total hysterectomy should be optimized. Meticulous follow-up, including the continuation of routine cervical cytological smears, is mandatory for patients with a retained cervix.